HIF1A and NFAT5 coordinate Na+-boosted antibacterial defense via enhanced autophagy and autolysosomal targeting. Issue 11 (2nd November 2019) - Neubert, Patrick; Weichselbaum, Andrea; Reitinger, Carmen; Schatz, Valentin; Schröder, Agnes; Ferdinand, John R.; Simon, Michaela; Bär, Anna-Lorena; Brochhausen, Christoph; Gerlach, Roman G.; Tomiuk, Stefan; Hammer, Karin; et al.
ABSTRACT: Infection and inflammation are able to induce diet-independent Na + -accumulation without commensurate water retention in afflicted tissues, which favors the pro-inflammatory activation of mouse macrophages and augments their antibacterial and antiparasitic activity. While Na + -boosted host defense against the protozoan parasite Leishmania major is mediated by increased expression of the leishmanicidal NOS2 (nitric oxide synthase 2, inducible), the molecular mechanisms underpinning this enhanced antibacterial defense of mouse macrophages with high Na + (HS) exposure are unknown. Here, we provide evidence that HS-increased antibacterial activity against E. coli was neither dependent on NOS2 nor on the phagocyte oxidase. In contrast, HS-augmented antibacterial defense hinged on HIF1A (hypoxia inducible factor 1, alpha subunit)-dependent increased autophagy, and NFAT5 (nuclear factor of activated T cells 5)-dependent targeting of intracellular E. coli to acidic autolysosomal compartments. Overall, these findings suggest that the autolysosomal compartment is a novel target of Na + -modulated cell autonomous innate immunity. Abbreviations : ACT: actins; AKT: AKT serine/threonine kinase 1; ATG2A: autophagy related 2A; ATG4C: autophagy related 4C, cysteine peptidase; ATG7: autophagy related 7; ATG12: autophagy related 12; BECN1: beclin 1; BMDM: bone marrow-derived macrophages; BNIP3: BCL2/adenovirus E1B interacting protein 3; CFU: colony forming units; CM-H2 DCFDA: 5-(and-6)-chloromethyl-2′, 7′-dichlorodihydrofluorescein diacetate, acetyl ester; CTSB: cathepsin B; CYBB: cytochrome b-245 beta chain; DAPI: 4, 6-diamidino-2-phenylindole; DMOG: dimethyloxallyl glycine; DPI: diphenyleneiodonium chloride; E. coli: Escherichia coli ; FDR: false discovery rate; GFP: green fluorescent protein; GSEA: gene set enrichment analysis; GO: gene ontology; HIF1A: hypoxia inducible factor 1, alpha subunit; HUGO: human genome organization; HS: high salt (+ 40 mM of NaCl to standard cell culture conditions); HSP90: heat shock 90 kDa proteins; LDH: lactate dehydrogenase; LPS: lipopolysaccharide; Lyz2/LysM: lysozyme 2; NFAT5/TonEBP: nuclear factor of activated T cells 5; MΦ: macrophages; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MFI: mean fluorescence intensity; MIC: minimum inhibitory concentration; MOI: multiplicity of infection; MTOR: mechanistic target of rapamycin kinase; NaCl: sodium chloride; NES: normalized enrichment score; n.s.: not significant; NO: nitric oxide; NOS2/iNOS: nitric oxide synthase 2, inducible; NS: normal salt; PCR: polymerase chain reaction; PGK1: phosphoglycerate kinase 1; PHOX: phagocyte oxidase; RFP: red fluorescent protein; RNA: ribonucleic acid; ROS: reactive oxygen species; sCFP3A: super cyan fluorescent protein 3A; SBFI: sodium-binding benzofuran isophthalate; SLC2A1/GLUT1: solute carrier family 2 (facilitated glucose transporter), member 1; SQSTM1/p62: sequestosome 1; ULK1: unc-51 like kinase 1; v-ATPase: vacuolar-type H + -ATPase; WT: wild type